(untitled) (Fiep Bulletin - online, 2013)
The purpose of this study was to verify if stretching exercises as preparatory activity for these athletes decrease the performance of the one repetition maximum (1-RM).The sample it was composed 12 female volleyball athletes with mean age, height, body mass (±SD) were 19,6 ± 2,1years; 68,2 ± 4,8 Kg; 177 ± 0,06 cm, respectively, all the subjects signed an informed consent form. They performed 3-test sessions of 1-RM (interval of 48 h among all sessions).The first one was of familiarization and the other two were of experimentation, with and without stretching exercises. The squat exercise was selected and performed in a smith machine, by the proximity to the movement of volleyball jump. In the first experimental session (session 1) the athletes ran for 10 minutes in a self-selected velocity and performed stretching exercises (2 repetitions, 15 seconds stretch) for lower limbs muscles (passive static stretching exercises=maximum gluteus(1), hamstring(1) quadriceps(1) and calf(1), active static exercises=quadriceps(1), hamstring(1) and calf(1)). Thereafter the athletes were submitted the 1-RM test. In the session 2 the athletes repeated the session 1 procedure, without the stretching exercises program. An alpha level of p<0,05 was considered significant. The experimental sessions were randomized. To compare the 1-RM performance between session 1 and 2 a paired t-test was used. Significant difference was not found in 1-RM (p< 0,389). The stretching exercises have not negative influence in 1-RM performance of these volleyball athletes.